Pembuatan LKPD berbasis komik model guided discovery learning pada materi usaha, energi, momentum, dan impuls kelas X SMA/MA - Rina Desriyenti; Gusnedi Gusnedi (Universitas Negeri Padang, 2020)
This study was conducted to determine the level of validity on the worksheet of students based on comic models guided discovery learning on business material, energy, momentum, and impulse for grade 10 high school or equivalent. The method used in this research is research and development using 4D developed by Thiagarajan. In this study will be determined until the development stage, so that only through 3 stages, namely define, design, and develop. The object used in this study is a worksheet of students based on comic models guided discovery learning on business material, energy, momentum, and impulse. Data obtained from this study were obtained from the validity test through the validity sheet. The validity sheet contains four components distributed by five validators. Data obtained from the validator were processed using the kappa moment equation (k), and the results obtained were 0.79, which was included in the high category. This shows that the worksheet of students based on comic models guided discovery learning on business material, energy, momentum, and impulse for grade 10 high school is valid.